Neonatal Bladder-derived Mesenchymal Stem Cells Ameliorate Bladder Dysfunction in Diabetic Rat Models - Boga, Mehmet Salih; Haliloğlu , Ahmet Hakan; Gülpınar, Ömer; Özayar, Asım; Sönmez, Mehmet Giray; Pinarli, Ferda Alpaslan; Boğa, Emre; Pinarci, Tangül; Tiryaki, Meral; Göğüş, Orhan (Urology Journal, 2020)
Purpose: To evaluate the effect of a new mesenchymal stem cell type derived from the neonatal bladder (nMSC-B) on diabetic bladder dysfunction (DBD). Materials and Methods: nMSC-B were harvested from neonatal male Sprague-Dawley rat’s bladder and expanded in culture. nMSC-B were transferred to Type-1 diabetic rats which were induced by a single dose 45 mg/kg Streptozocin (STZ). Stem cells were transferred via intraperitoneally (IP) (DM-IP group, n:6) and by direct injection to the detrusor (DM-D group, n:6) at 12th week following diabetes and compared with Phosphate Buffered Saline (PBS) injected diabetic rats (DM-PBS group, n:6) and age-matched PBS injected non-diabetic normal rats (NR-PBS group, n:6). All rats were evaluated histopathologically and functionally four weeks after the stem cell treatment. Results: nMSC-B showed improvement in both voiding function and bladder structure. The maximum voiding pressure (MVP) values in the DM-PBS group were lower compare to DM-IP, DM-D and NR-PBS groups (13.27 ± 0.78 vs 16.27 ± 0.61, 28.59 ± 2.09, 21.54 ± 1.00, respectively, P < .001). There was a significant improvement for MVP values in stem cell-treated groups. Immunohistochemical examination revealed decreased bladder smooth muscle (SM), increased fibrosis and desquamation in urothelia in diabetic groups compared to normal group(P < .001). We detected recovery in the stem cell groups. This recovery was more evident in DM-D group. No statistical difference was observed in SM and fibrosis between DM-D and NR-PBS groups (P = .9). Conclusion: It was shown that nMSCBs provided amelioration of DBD. We think that nMSC-B constitutes an effective treatment method in DBD.